Analisis Ekspresi BRAF dan TERT pada Kasus Papillary Thyroid Carcinoma Berdasarkan Stratifikasi Risiko ATA - Cempaka Harsa Sekarputri,; Etty Hary Kusumastuti,; Gondo Mastutik (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2020)
BackgroundPapillary thyroid carcinoma (PTC) is the most common malignancy in thyroid, accounting for more than 80% of all thyroid cancer.Rrecurrences of the disease reach 30% cases. It has been widely observed that BRAF and TERT is associated with aggressivenessbehaviors in human cancer. Both are involved in the pathogenesis of PTC that may be used as targets for new therapies. AmericanThyroid Association (ATA) risk stratification can define the risk of recurrence in PTC. No marker has been found to determine therisk of PTC recurrence. The purpose of this study is to analyzed BRAF and TERT expression in ATA risk stratification system inPTC classic variant samples.MethodsThe methods of this study is an analytical observational study with cross sectional approach, conducted on 56 samples of PTCclassic variant selected from Department of Anatomical Pathology Dr. Soetomo General Hospital between January 2015-December2017 by determined criteria in ATA risk stratification groups of low risk, intermediate risk and high risk. The expression BRAF andTERT observed using immunohistochemical staining of Santa Cruz monoclonal antibody.ResultsThe result for each group based on ATA risk stratification groups of low risk were 13 samples (23.20%), intermediate risk were 25samples (44.62%) and high risk were 18 samples (32.12%).The correlation was assessed with Spearman’s rho correlation test. There is significant correlation BRAF (p=0.004) with a value ofr=0.374 and TERT(p=0.032) with a value of r=0.287 for ATA risk stratification.ConclusionBRAF and TERT expression showed significant correlation to ATA risk stratification in classic variant PTC.